0D–1D hybrid nanoarchitectonics: tailored design of FeCo@N–C yolk–shell nanoreactors with dual sites for excellent Fenton-like catalysis. Issue 46 (18th November 2021) - Wang, Chaohai; Wang, Hongyu; Na, Jongbeom; Yao, Yiyuan; Azhar, Alowasheeir; Yan, Xin; Qi, Junwen; Yamauchi, Yusuke; Li, Jiansheng
Abstract : Novel 0D–1D hybrid nanoarchitectonics consisting of FeCo@N–C yolk–shell nanoreactors are developed for Fenton-like reaction. With the multilevel advantages of this design, FeCo@N–C nano-necklaces exhibit excellent performance for BPA removal. Abstract : Heterogeneous Fenton-like processes are very promising methods of treating organic pollutants through the generation of reactive oxygen containing radicals. Herein, we report novel 0D–1D hybrid nanoarchitectonics (necklace-like structures) consisting of FeCo@N–C yolk–shell nanoreactors as advanced catalysts for Fenton-like reactions. Each FeCo@N–C unit possesses a yolk–shell structure like a nanoreactor, which can accelerate the diffusion of reactive oxygen species and guard the active sites of FeCo. Furthermore, all the nanoreactors are threaded along carbon fibers, providing a highway for electron transport. FeCo@N–C nano-necklaces thereby exhibit excellent performance for pollutant removal via activation of peroxymonosulfate, achieving 100% bisphenol A ( k = 0.8308 min −1 ) degradation in 10 min with good cycling stability. The experiments and density-functional theory calculations reveal that FeCo dual sites are beneficial for activation of O–O, which is crucial for enhancing Fenton-like processes.